Market-based governance within the walls of the state: the state guarantee model as a market-based governance mode in Danish transport infrastructure - Christensen, Lene (Politica, 2022)
The article contributes to the Danish literature on public governance by presenting, analyzing and conceptualizing a widespread yet overlooked governance mode that will become even more influential in the future infrastructure policy. The article explores: How has the state guarantee model (SGM) developed into a market-based governance mode in the Danish infrastructure governance in the transport area, which is dominated by a hierarchal governance paradigm? The article is based on a qualitative case study of all infrastructure projects with SGM using the concept of governance paradigms adapted to the area of infrastructure. The article shows that SGM is invented to realize mega-projects outside the bureaucratic governance mode. The development from governance model to governance mode takes place as new public companies emerge and contribute with expertise and funding to the existing infrastructure network based on a bureaucratic governance mode. Over time, the model is further developed for public transport and medium-sized infrastructure projects in hybrid models that lead to changes in the norms for user charges in the hierarchal governance paradigm. Over time, the SGM reduces political control over existing and new SGM projects.